Volcanoes - Branley, Franklyn Mansfield, 1915-2002.; Lloyd, Megan (New York : Collins, 2008)
Provides accounts of some of the worst volcano disasters in history, and includes information about why and where volcanoes occur, and the types of damage they cause.
3.3
K-3
Keywords: Volcanoes -- Juvenile literature; Volcanoes; Volcanoes